Effects of probiotics, prebiotics, and synbiotics on the growth performance, biochemical indexes, and gut morphometry of turkeys - Sulaiman, A. S.; Hussaini, B. A.; Uyanga, V. A. (Frontiers in Physiology, 2025)
This study investigated the effects of dietary supplementation with probiotics, prebiotics, or synbiotics on the growth performance, immune function, and gut health in turkeys. A total of 180 turkeys were allocated into four dietary groups: basal diet (control group); basal diet supplemented with 1.0 × 108 CFU/g Lactobacillus acidophilus and Bacillus subtilis 1.0 × 108 CFU/g (Probiotic group); basal diet supplemented with 1% inulin and 0.5% Mannan oligosaccharides (Prebiotic group) or basal diet supplemented with both prebiotic and probiotic mixtures (Synbiotic group), and fed for 12 weeks. Growth performance was evaluated at 4–10 weeks (phase 1) and 10–16 weeks (phase 2), then blood and tissue samples were collected at the end of the study to assess immunological, biochemical parameters, and intestinal morphometry. Compared to the control group, the body weight gain of the probiotics and synbiotic groups were significantly higher at phase 2 (P < 0.05), and this persisted with synbiotic supplementation during the overall phase (P = 0.05). Similarly, the feed intake of turkeys during the overall phase was improved in the probiotic, prebiotics and synbiotics groups compared to the control group (P < 0.05). Carcass yield remained unaffected, but the spleen and bursa weights were significantly higher in the probiotics and synbiotic groups (P < 0.05). Blood analysis revealed elevated white blood cell counts and total cholesterol in turkeys fed probiotic, prebiotics and synbiotics relative to the control group (P < 0.05). Duodenal morphology showed no significant differences among treatment groups, whereas, the Lactobacillus counts were significantly higher in probiotics and synbiotics-fed turkeys compared to the control group (P < 0.05). Crude protein digestibility was higher with prebiotics and synbiotics supplementation, and the probiotic diet further increased nitrogen retention in turkeys (P < 0.05), compared to the control group. Additionally, behavioral assessments indicated increased activity of synbiotics-fed turkeys compared to the control group (P < 0.05). Overall, synbiotics emerged as an effective dietary intervention, providing the synergistic actions of both pre- and probiotics on the growth performance, immune functioning, and nutrient utilization, thus, underscoring their potential as a strategic nutritional supplement for turkey production.